1985
DOI: 10.1099/00221287-131-10-2753
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Mapping of Escherichia coli K12 Mutants Defective in Phenylacetate Degradation

Abstract: Mutants of Escherichia coli K12 unable to grow on phenylacetate have been isolated and mapped. The mutations were located in the relatively 'silent' region of the E. coli K12 chromosome at min 30.4 on the genetic map, with the gene order racpac-I pac-2 trg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…5A), which is involved in the transformation of PEA into PA (see below), at 31.1 min near the replication terminus of the chromosome (94). This location confirms previous observations that mapped the mutations in two PA-deficient mutants of E. coli K-12 in this chromosomal region (48). Although the left end of the paa cluster is adjacent to the maoA gene both in E. coli W and K-12, the right end of this cluster differs in these two strains.…”
Section: Pa Catabolic Pathwaysupporting
confidence: 75%
See 1 more Smart Citation
“…5A), which is involved in the transformation of PEA into PA (see below), at 31.1 min near the replication terminus of the chromosome (94). This location confirms previous observations that mapped the mutations in two PA-deficient mutants of E. coli K-12 in this chromosomal region (48). Although the left end of the paa cluster is adjacent to the maoA gene both in E. coli W and K-12, the right end of this cluster differs in these two strains.…”
Section: Pa Catabolic Pathwaysupporting
confidence: 75%
“…However, 2HPA appears not to be a true intermediate in the PA catabolic pathway since it does not support the growth of E. coli W and is not consumed even when E. coli W cells are growing also in the presence of PA (94). A similar lack of growth on 2HPA and accumulation of this compound after addition of PA to some cultures of PA-deficient mutant strains from E. coli K-12 (48) and P. putida U (217), has been also observed. Although the possibility that exogenous 2HPA does not enter the cells cannot be ruled out, the fact that 2HPA formation requires the simultaneous expression of the paaK and paaABCDE genes strongly suggests that 2HPA is not a true intermediate in PA degradation but is derived from the accumulation of a hydroxylated PA-CoA intermediate that cannot be further degraded.…”
Section: Pa Aerobic Hybrid Pathwaymentioning
confidence: 68%
“…1) 4. UV absorption spectra associated with the spontaneous enol-keto isomerization of HHDD in 0.1 M sodium phosphate buffer (pH…”
Section: Discussionmentioning
confidence: 99%
“…Phage-mediated transductions have show'n that chromosomal genes for particular aromatic catabolic pathways are tightly clustered both in Pseudomonas species and in E. coli (4,21,32). The most detailed studies of clustered aromatic catabolic pathway genes are those of plasmids such as the TOL plasmid pWWO and the NAH plasmid pIG7.…”
Section: Discussionmentioning
confidence: 99%
“…4 indicated that E. coli B/rK (a UV-resistant derivative of the wild-type B strain supplied by M. Vicente), E. coli C (a wild-type strain supplied by M. Vicente), and E. coli W (a wild-type strain from R. A. Cooper laboratory stock supplied by A. Garrido-Pertierra), as well as K. pneumoniae MWal (strain UN, supplied by A. Garrido-Pertierra) (30) and Kluyvera citrophila ATCC 21285 (penicillin G acylase producer) (16), contained DNA sequences homologous to hpaB. However, the genomes of two different E. coli K-12 strains, DH1 and W3110 (CECT 416, ATCC 27325) (36), did not contain any homologous DNA fragment, which suggests that hpaB is not a gene involved in the pathway of phenylacetic acid in these strains (9). On the contrary, the hybridization observed with the other strains might indicate that hpaB is a gene involved in 4-HPA degradation, since all of these strains are able to metabolize 4-HPA, a characteristic not shared by K-12 strains (8).…”
mentioning
confidence: 99%